Retos y perspectivas de la Universidad Técnica de Machala ante la transformación curricular de la Educación Superior Ecuatoriana. - Riofrío Orozco, Oscar (2015)
The current trend of the Ecuadorian higher education is continuous improvement, leading to the preparation of men for life. In this regard, the academic models should consider the epistemological understanding trends in Latin America and globally, to make relevant institutions universities. To do this, the changes to be operated have to integrate the transition from disciplinary knowledge, inter and transdisciplinary, uniformity of actors and areas of application of knowledge, heterogeneity, circuit production closed and decontextualized knowledge, open circuits and application contexts. Faced with this challenge the academic direction of the design UTMach Improvement project, the results of their progress are presented from the analysis of the challenges and perspectives front to respond to the imperative of Ecuadorian higher education to the curriculum transformation their academic programs.